Representasi Premanisme dalam Film Pendek Loz Jogjakartoz (Analisis Semiotika Roland Barthes) - Risdarminto, Ryo Riandika; Nanda, Ertika (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research was conducted with the aim of knowing and explaining the representation of thuggery shown in the Loz Jogjakartoz short movie. Thuggery is one of the most familiar issues in Indonesia. This research is a qualitative research using analysis technique Roland Barthes' semiotic theory. The results of this research are the analysis denotative, connotative, and mythological meanings. In addition to a thug, thuggis behavior is also demonstrated by detective and liquor seller. The representation of thuggery in the Loz Jogjakartoz short movie depicts thugs who do not look exactly like the stereotypical image of thugs understood by society, which is that thugs must have tattoos, piercing, long hair, behave rudely, get drunk, and wear leather jackets. However in this movie, the representation of thuggery is only shown through aspects of having piercing, wear leather jacket, and behaving rudely.